Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.3109/13813459009115735
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous electromechanical activity in the rat duodenumin vitro

Abstract: Isolated rat duodenum shows spontaneous mechanical and electrical activities. Mechanical activity consists in changes both in endoluminal pressure and in isometric tension. Electrical activity is characterized by slow waves with superimposed bursts. This spontaneous activity is tetrodotoxin (TTX) resistant and therefore it is myogenic in origin. Indeed, TTX pretreatment, even in the presence of atropine and guanethidine, caused an increase in amplitude and in frequency of the electrical and mechanical activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…Our results regarding the rate of occurrence of longitudinal contractions in the duodenum of the rat do not allow such distinction. The frequency of the fast phasic longitudinal contractions obtained in our study was close to that previously reported in an ex vivo manometric study of a 2 cm length of rat duodenum (33.4 ± 1.62 cpm) and to the slow wave frequency in the same preparation (34.2 ± 4.4 cpm) 24 . It was also similar to that in the rat (27 cpm), 36 which was reported to be unmodified following addition of tetrodotoxin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results regarding the rate of occurrence of longitudinal contractions in the duodenum of the rat do not allow such distinction. The frequency of the fast phasic longitudinal contractions obtained in our study was close to that previously reported in an ex vivo manometric study of a 2 cm length of rat duodenum (33.4 ± 1.62 cpm) and to the slow wave frequency in the same preparation (34.2 ± 4.4 cpm) 24 . It was also similar to that in the rat (27 cpm), 36 which was reported to be unmodified following addition of tetrodotoxin.…”
Section: Discussionsupporting
confidence: 90%
“…Later work showed that segmentation could involve both circular and longitudinal musculature 14 and was induced by nutrients such as decanoic acid 8 . Moreover, it was postulated that segmental contractions are regulated by elements of the enteric nervous system (ENS) 12,22–25 . Work also showed that segmental contractions may be progenitors of peristaltic contraction as some may propagate a short distance along the duodenum while others could propagate for longer distances 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The contractions consisted of homogeneous waves. Consistent with previous reports [4,16,17] , we confi rmed that tetrodotoxin (0.1 mol/l) did not abolish spontaneous rhythmic contractions, suggesting the basal mechanical activities were not neuronal in origin (data not shown).…”
Section: Basal Contractile Activitysupporting
confidence: 80%
“…Waxing and waning of slow waves in intestinal musculature results in high (wax) and low (wane) open probability for Ca 2+ channels, and has been previously recorded in other areas of the gastrointestinal tract and species such as the cat small intestine, the porcine ileum, the rat duodenum or the human colon . Diamant and Bortoff already in 1969 suggested that the wax and wane phenomenon could be possibly attributed to the interaction of two competing pacemakers, but they believed these pacemakers were both the slow wave generating pacemakers.…”
Section: Electrical and Mechanical Features Of Each Predicted Motor Pmentioning
confidence: 92%